Pathogenesis and treatment of Sjogren’s syndrome: Review and update - Zhan, Qipeng; Zhang, Jianan; Lin, Yubin; Chen, Wenjing; Fan, Xinzou; Zhang, Dunfang (Frontiers in Immunology, 2023)
Sjogren’s syndrome (SS) is a chronic autoimmune disease accompanied by multiple lesions. The main manifestations include dryness of the mouth and eyes, along with systemic complications (e.g., pulmonary disease, kidney injury, and lymphoma). In this review, we highlight that IFNs, Th17 cell-related cytokines (IL-17 and IL-23), and B cell-related cytokines (TNF and BAFF) are crucial for the pathogenesis of SS. We also summarize the advances in experimental treatment strategies, including targeting Treg/Th17, mesenchymal stem cell treatment, targeting BAFF, inhibiting JAK pathway, et al. Similar to that of SLE, RA, and MS, biotherapeutic strategies of SS consist of neutralizing antibodies and inflammation-related receptor blockers targeting proinflammatory signaling pathways. However, clinical research on SS therapy is comparatively rare. Moreover, the differences in the curative effects of immunotherapies among SS and other autoimmune diseases are not fully understood. We emphasize that targeted drugs, low-side-effect drugs, and combination therapies should be the focus of future research.